EVALUASI SENSORI DAN KIMIA SNACK BAR BERBAHAN BAKU TEMPE DAN KURMA SEBAGAI MAKANAN PEMULIHAN PADA ENDURANCE SPORT - diandini andriani; Yuges Saputri (FoodTech: Jurnal Teknologi Pangan, 2019)
Endurance sport is a kind of sport which has main activities utilizes the strength of muscle endurance with a long duration. Those activities surely requires appropriate nutritional intake to restore the physical performance of athletes. The study aims to evaluate the sensory and chemical characteristics of snack bars developed from tempeh and dates. This experimental study used a completely randomized design (CRD) which utilized tempeh and Tunisian dates Deglet nour as the main raw materials. The Visual Analog Scale (VAS) method was used to determine the product sensory value; proximate analysis methods was used to determine the level of carbohydrate, protein, fat, water, and ash; and the electrolyte levels, namely Na + and K- were determined by the Atom Absorption Spectrophotometry (AAS) method. The result showed that there were no significant differences in sensory values among the formulation except “taste” parameters. Selected formulation F2 (Tempeh 85 g: Dates 215 g) contains 61.60% carbohydrate, 12.92% protein, 3.15% fat, 20.09% water, and 2.23% ash content and contains  Na+ about 0.8 mg / 100 g and K- about 4.18 mg / 100 g. Thus, the snack bar has a potential to be a recovery food of endurance sport athletes performance. However, it is suggested to study further of direct influence of snack bar consumption on the physical performance on endurance sport athletes.